Comprehensive analysis of the molecular characterization of GM rice G6H1 using a paired-end sequencing approach. (30th March 2020) - Zhang, Yuchen; Zhang, Hanwen; Qu, Zhan; Zhang, Xiujie; Cui, Jinjie; Wang, Canhua; Yang, Litao
Highlights: The full molecular characterization of one novel GM rice G6H1 was revealed. One new pipeline and formula for determining the exogenous DNA integration. Minimum resequencing data volume and depth for GMO molecular characterization analysis. Abstract: Molecular characterization of exogenous DNA integrations in host genome is a key aspect in risk assessment of bioengineered crops. However, gaining a clear understanding of the molecular characters of a bioengineered crop using conventional techniques remains a challenging task. Herein, we report the full molecular characterization of one new transgenic rice event G6H1 via a paired-end sequencing approach and bioinformatics analysis pipelines. Also, the molecular characterization reported was validated using conventional PCR, Sanger sequencing, and digital PCR. The results showed there is only one copy of the exogenous DNA inserted, which is located within chromosome 7 of the G6H1 genome. There is no other unintended integration of sequences from the transformation plasmid. These results indicated that the paired-end sequencing approach, combined with bioinformatics pipeline developed, is well suited to elucidate the molecular characteristics of bioengineered crops, and is efficient, low cost, and comprehensive.